2018
DOI: 10.1007/s00125-018-4719-7
|View full text |Cite
|
Sign up to set email alerts
|

Which is more important for cardiometabolic health: sedentary time, higher intensity physical activity or cardiorespiratory fitness? The Maastricht Study

Abstract: Aims/hypothesesOur aim was to examine the independent and combined (cross-sectional) associations of sedentary time (ST), higher intensity physical activity (HPA) and cardiorespiratory fitness (CRF) with metabolic syndrome and diabetes status.MethodsIn 1933 adults (aged 40–75 years) ST and HPA (surrogate measure for moderate to vigorous physical activity) were measured with the activPAL3. CRF was assessed by submaximal cycle–ergometer testing. Metabolic syndrome was defined according to the Adult Treatment Pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 39 publications
3
46
2
Order By: Relevance
“…Each of higher levels of total PA, greater lean mass, and higher vitamin D status were associated with lower risk of MetS in men and women. These results are consistent with other studies that have examined separately PA, lean mass and vitamin D as risk predictors for MetS or diabetes. By examining all these factors within a single study, we are able to compare the magnitude of associations between PA, lean mass and vitamin D with this outcome.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Each of higher levels of total PA, greater lean mass, and higher vitamin D status were associated with lower risk of MetS in men and women. These results are consistent with other studies that have examined separately PA, lean mass and vitamin D as risk predictors for MetS or diabetes. By examining all these factors within a single study, we are able to compare the magnitude of associations between PA, lean mass and vitamin D with this outcome.…”
Section: Discussionsupporting
confidence: 92%
“…Both increased availability of energy‐dense foods and increasingly sedentary lifestyles are implicated in MetS development . Conversely, higher levels of physical activity (PA) across a range of intensities are associated with reduced risk of MetS …”
Section: Introductionmentioning
confidence: 99%
“…In contrast, a previous study demonstrated that poor mobility with a high fall risk is linked to hyperglycemic status even in younger patients with a short duration of T2D [19]. Also, low cardiorespiratory fitness is associated with an increase in the risk of having metabolic syndrome and T2D, independent of physical activity and sedentary time [20]. Therefore, impaired physical ability in addition to physical inactivity and a sedentary lifestyle may warrant more attention from healthcare providers in terms of glycemic management individualized for each patient with T2D.…”
Section: Discussionmentioning
confidence: 74%
“…The first-day of data were excluded, and subsequent days were defined as the 24 hours between consecutive midnights. Only participants providing at least one valid day, defined as waking wear time more than 10 hours per day, were included for further analysis (13).…”
Section: Sedentary Behavior and Other Physical Activity Variablesmentioning
confidence: 99%
“…Thigh-worn accelerometry has better-established validity and reliability for measuring posture, activity intensity, and ambulatory movement in free-living conditions in adults (10)(11)(12). To date, the most extensive cross-sectional study using thigh-worn accelerometers (13) suggested that the odds ratios of metabolic syndrome and type 2 diabetes were higher in individuals with higher sedentary time or lower moderate-to-vigorous physical activity. Another relatively small-scale cross-sectional study (14) found that the number of breaks in sedentary time was beneficially associated with cardiometabolic health markers, e.g., body mass index, waist circumference, high-density lipoprotein cholesterol (HDL-C), and triglycerides (TG).…”
Section: Introductionmentioning
confidence: 99%